Basal transcription of human topoisomerase II : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biochemistry at Massey University - Magan, Natisha (Massey University, 2002)
Topoisomerase II is a ubiquitously expressed enzyme, which is required for cell survival. It has the ability to alter the topological states of DNA by introducing transient double-stranded breaks in DNA. Humans have two topoisomerase II isoforms, ɑ and β, and both are differentially expressed and localized. Tissues with rapidly proliferating cells exhibit elevated topoisomerase IIɑ gene expression whereas the β isoform is ubiquitously expressed amongst tissues. In addition to a role in cell survival, a number of anti-cancer drugs have been shown to target human topoisomerase II in vivo. However, the development of drug resistance is a major clinical problem; for example, approximately 60% of breast cancers treated with the topoisomerase II poison doxorubicin become resistant to this drug. Down-regulation of topoisomerase II is thought to be one of the factors involved in the development of drug resistance, where the relative levels of topoisomerase IIɑ and topoisomerase IIβ in cells is thought to effect drug efficacy. The expression of topoisomerase IIɑ and β is regulated at the transcriptional level, through binding of transcription factors to specific elements within the promoter sequence. Therefore investigating the transcriptional regulation of both isoforms could lead to an understanding of the mechanisms involved in the development of drug resistance. The initial aim of this study was to isolate a fragment of the upstream regulatory sequence of the topoisomerase IIβ gene and carry out systematic analysis of this sequence. However, this could not be pursued, as the clones that were examined did not contain the required topoisomerase IIβ sequence. This study progressed to examine the relevance of three elements (GC1, ICB1 and GC2) within the topoisomerase IIɑ minimal promoter and the importance of the cognate transcription factors NF-Y, Spl and Sp3 in regulating the expression of the topoisomerase IIɑ gene. Electrophoretic mobility shift assays and transient transfection assays were used to study protein/DNA interactions and the functional significance of these interactions, respectively. Both NF-Y and Spl were shown to activate the transcriptional regulation of topoisomerase IIɑ by binding to their respective elements; in addition functional interactions between the two proteins bound to the promoter was observed.
Keywords: DNA topoisomerase II